Lessons learned from the experiences and perspectives of frontline healthcare workers on the COVID-19 response: a qualitative descriptive study - Marian Orhierhor; Wendy Pringle; Donna Halperin; Janet Parsons; Scott A. Halperin; Julie A. Bettinger (BMC, 2023)
Abstract Background During the COVID-19 pandemic, healthcare systems and healthcare workers (HCWs) faced significant demands and unique challenges. In this qualitative study, we explore the effects of the COVID-19 public health policies on British Columbia's frontline HCWs, describe what worked in the management of the pandemic, and elucidate the lessons learned that could be applied to future pandemic preparedness, recovery and response. Methods This qualitative descriptive study is part of a larger, national multi-case study on pandemic policy communication and uptake. Semi-structured interviews were conducted from November 2020- June 2021 with fourteen HCWs working in long-term care (LTC), acute care and public health settings. Data were inductively coded, and analyzed following a resilience framework for public health emergency preparedness, which emphasizes the essential elements of a public health system, vital to all phases of health emergency management, readiness, response and recovery. Results HCWs experienced confusion, frustration, uncertainty, anxiety, fatigue and stress, during the pandemic and detailed challenges that affected policy implementation. This included communication and coordination inconsistencies between the province and regional health authorities; lack of involvement of frontline staff in pandemic planning; inadequate training and support; inadequate personal protective equipment resource capacity and mobilization; and staffing shortages. HCWs recommended increased collaboration between frontline staff and policy makers, investment in preparing and practicing pandemic plans, and the need for training in emergency management and infection prevention and control. Conclusions Pandemic planning, response and recovery should include inputs from actors/key stakeholders at the provincial, regional and local levels, to facilitate better coordination, communication and outcomes. Also, given the critical roles of frontline HCWs in policy implementation, they should be adequately supported and consideration must be given to how they interpret and act on policies. Bi-directional communication channels should be incorporated between policymakers and frontline HCWs to verify the appropriate adoption of policies, reflective learning, and to ensure policy limitations are being communicated and acted upon by policy makers.